The Ethnic Group Role With Stunting Incidents In Sekip Village Lubuk Pakam District - Sri Melda Br Bangun; Windi Anggreni Sitepu (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2023)
Stunting is a condition where toddlers have less length and height compared to their peers. Stunting is one of the focuses of the 2nd Sustainable Development Goals (SDGs), namely eliminating hunger and all forms of malnutrition by 2030 and achieving food security. The World Health Organization (WHO) sets a maximum limit of 20% or one fifth of the total number of toddlers. This study aims to determine the role of local culture in the incidence of stunting in Sekip Village, Lubuk Pakam District. This type of quantitative research, is an analytic survey with a cross sectional design. The sample size is 62 mothers who have toddlers with a purposive sampling technique, using a questionnaire sheet. Based on the results of the Chi Square test it was found that local culture played a role in stunting with a value of p = 0.017 <? (0.05). The conclusion of this study is that culture has a role in the incidence of stunting. Suggestions for cross-sectoral collaboration involving community leaders in the context of providing education about stunting